Discourse of Conflict between Corruption Eradication Commission (KPK) Versus Indonesia Police (Polri) at kompas.com - Qathrunnada, Zalfa; Nugroho, Catur (Future Science, 2024)
In eradicating corruption, KPK is required to be the central institution that plays a crucial role in overcoming corrupt practices at various levels of society. Ironically, this corruption phenomenon has involved KPK members, even the highest leadership of the 2019-2023 KPK chairman named Firli Bahuri, who was decided as a corruption suspect on November 22, 2023, and became history in Indonesia. The incident highlighted the complexities and challenges faced by this anti-corruption agency and attracted the attention of many parties, including the media. Kompas.com is the most trusted media platform for Indonesians in 2023 and has quite a lot of news intensity about Firli Bahuri's resistance. Therefore, this research aims to reveal Kompas.com in producing texts, to find Kompas.com in producing discourse based on ideology and media interests, and to find Kompas.com in building perspectives and representations based on the external context of media and politics in Indonesia. The author uses Fairclough's Critical Discourse Analysis (CDA) method for this research. The research shows that Kompas.com's dominant discourse attempts to maintain balance by using many direct quotes from official sources and focusing on the legal process. Kompas avoids direct criticism of Firli or other parties involved in the case. By not highlighting the allegations or evidence against Firli in-depth, Kompas is trying to maintain neutrality and not appear to favor one side. However, this could be interpreted as a form of veiled support.